Implementation of the Internal Quality Assurance System on the Quality of Learning Planning and Implementation in State Vocational High Schools - Adi Suandi Sihombing; Tubagus Pamungkas; Hermansah Hermansah (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to analyze the implementation of the Internal Quality Assurance System (IQAS) and its relationship with the quality of learning planning and implementation in a state vocational high school in Batam. The study employed a concurrent mixed-methods approach in which quantitative and qualitative data were collected simultaneously. Quantitative data were obtained through questionnaires and analyzed using descriptive statistics and Pearson correlation, while qualitative data were gathered through interviews, observations, and documentation studies and analyzed thematically. The findings revealed that the implementation of IQAS was categorized as moderate to good. The quality of learning planning was considered fairly good, particularly in the alignment of learning instruments with the curriculum, while the quality of learning implementation was also moderate, especially in classroom management and teaching methods. Correlation analysis indicated a positive relationship between IQAS implementation and the quality of learning planning and implementation. Qualitative findings supported these results, although challenges remained in the evaluation and follow-up stages. The study confirms that IQAS plays a strategic role in improving the quality of learning in vocational schools